Phenotypic and genetic parameters of growth traits of blended goats at Malya, Tanzania - Das, S.M.; Rege, J.E.O.; Shibre, M. (International Livestock Research Institute, 1996)
Twenty-five year (1965-89) data on the Blended goats from Malya Research Centre totalling 4799 records were analysed for live weights and growth traits from birth to 72 weeks of age. The Blended goat developed in Malya, Tanzania, is a stabilised three-way cross of the Kamorai (55%), Boer (30%) and indigenous (15%) goats. Birth weight and weaning weight (16 weeks) averaged 2.47±0.02 kg and 11.14±0.15 kg, respectively. Live weights at 24, 48 and 72 weeks of age averaged 12.47±0.26 kg, 16.42±0.32 kg and 25.800.43 kg, respectively. Average daily gain from birth to weaning, and to 24,48 and 72 weeks of age averaged 80.0±1.0 g, 59±2 g, 41±1 g and 46±1 g, respectively. Year of birth, sex of kid and type of birth significantly (P<0.001) affected birth weight, weaning weight and live weight at 24, 48 and 72 weeks of age. Season of birth significantly (P<0.01) affected birth weight and live weight at 48 and 72 weeks of age. Age of dam significantly (P<0.01) affected birth weight and weight at 48 weeks of age. Heritability estimates for birth weight, weaning weight and weight at 24 weeks were 0.0151±0.036, 0.099±0.39 and 0.0148±0.053, respectively. Repeatability estimates for birth weight, weaning weight and weights at 24, 48 and 72 weeks of age were 0.202±0.18, 0.1870.22, 0.533±0.022, 0.0160.035 and 0.174±0.38, respectively.